Comparative assessment of physicians’ and senior medical students’ basic knowledge in treatment of chronic obstructive pulmonary disease - Roman A. Bontsevich; Tatiana S. Filinichenko; Yana R. Vovk; Anna A. Gavrilova; Galina G. Prozorova; Natalya Y. Goncharova; Olga V. Cherenkova; Olga G. Kompaniets; Andrey A. Kirichenko; Elizaveta Y. Ebzeeva; Galina G. Ketova; Valeriya O. Barysheva; et al. (Research Results in Pharmacology, 2019)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the most common pathologies of the respiratory system. This disease ranks third in the group of the main causes of death in the world. The effective treatment of COPD has been developed by today. However, a significant part of physicians has an insufficient amount of education in this matter.